Determination method using gene polymorphism - YOSHIMOTO TAKESHI; KAWAKAMI DAISUKE; IHARA MASAFUMI (2024)
Provided are: a method for predicting intracranial brain vessel reocclusion, the method comprising: a step for detecting, using a sample collected from a subject, whether or not the subject has RNF213p. R4810K polymorphism; and a step in which, when the subject has the RNF213p. R4810K polymorphism, it is determined that after an intravascular treatment for an intracranial cerebral vascular occlusion, the possibility of a reocclusion of a blood vessel, which has been subjected to the intravascular treatment, is high. 提供：用于预测颅内脑部血管再闭塞的方法，其包括如下步骤：使用从被检者采集的样品来检测前述被检者是否具有RNF213p.R4810K多态性的步骤；以及，在前述被检者具有前述RNF213p.R4810K多态性时，判定为在针对颅内脑部血管闭塞的血管内治疗后接受了前述血管内治疗的血管发生再闭塞的可能性高的步骤。